Limited cerebellar gradient extension in temporal lobe epilepsy with dystonic posturing - Wei Li; Junxia Chen; Yingjie Qin; Sisi Jiang; Xiuli Li; Heng Zhang; Cheng Luo; Qiyong Gong; Dong Zhou; Dongmei An (Epilepsia Open)
Abstract Objective Dystonic posturing (DP) is a common semiology in temporal lobe epilepsy (TLE). We aimed to explore cerebellar gradient alterations in functional connectivity in TLE patients with and without DP. Methods Resting‐state functional MRI data were obtained in 60 TLE patients and 32 matched healthy controls. Patients were further divided into two groups: TLE with DP (TLE + DP, 31 patients) and TLE without DP (TLP‐DP, 29 patients). We explored functional gradient alterations in the cerebellum based on cerebellar–cerebral functional connectivity and combined with independent component analysis to evaluate cerebellar–cerebral functional integration and reveal the contribution of the motor components to the gradient. Results There were no obvious differences in clinical features and postoperative seizure outcomes between TLE + DP and TLE‐DP patients. Patients and controls all showed a clear unimodal‐to‐transmodal gradient transition in the cerebellum, while TLE patients demonstrated an extended principal gradient in functional connectivity compared to healthy controls, which was more limited in TLE + DP patients. Gradient alterations were more widespread in TLE‐DP patients, involving bilateral cerebellum, while gradient alterations in TLE + DP patients were limited in the cerebellum ipsilateral to the seizure focus. In addition, more cerebellar motor components contributed to the gradient alterations in TLE + DP patients, mainly in ipsilateral cerebellum. Significance Extended cerebellar principal gradients in functional connectivity revealed excessive functional segregation between unimodal and transmodal systems in TLE. The functional connectivity gradients were more limited in TLE + DP patients. Functional connectivity in TLE patients with dystonic posturing involved more contribution of cerebellar motor function to ipsilateral cerebellar gradient. Plain Language Summary Dystonic posturing contralateral to epileptic focus is a common symptom in temporal lobe epilepsy, and the cerebellum may be involved in its generation. In this study, we found cerebellar gradients alterations in functional connectivity in temporal lobe epilepsy patients with and without contralateral dystonic posturing. In particular, we found that TLE patients with dystonic posturing may have more limited cerebellar gradient in functional connectivity, involving more contribution of cerebellar motor function to ipsilateral cerebellar gradient. Our study suggests a close relationship between ipsilateral cerebellum and contralateral dystonic posturing.